(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In this study, measurement of alpha emitters such as radon-222, radium-226, and uranium-238 levels in Iraqi of medical plants samples using CR-39 detector. As well as, annual average internal dose (AAIED) and risk of an excess cancer fatality per million persons (RECFPMP) due to ingestion of radon, radium, and uranium from samples in the present study were calculated. The average values with stander error of radon-222, radium-226, and uranium-238 activity in unit Bq/kg were 5.22 ±0.94, 0.3409 ±0.061, and 5.20 ±0.942, respectively. While, the average values of AAIED and RECFPMP due to alpha emitters in all samples of medical plants were 0.348±0.063 μSv/y and 1.21±0.221, respectively. Analysis of samples has been studied and therefore compared with the internationally published and permissible range that has been recommended by the international scientific committees. Accordingly, it was found that radiation levels in medicinal herbs available in local markets were fallen within natural and allowed limits and therefore don't impose any danger out of the radioactive aspect in terms of human consumption and use of medical treatment.